Fabrication of metal oxide nanobranches on atomic-layer-deposited TiO2 nanotube arrays and their application in energy storage - Xia, Xinhui (2013)
Due to the chemical stability and easy fabrication by atomic layer deposition (ALD), TiO2 nanotubes are regarded highly useful in constructing branched nanostructured electrodes for solar conversion and electrochemical energy storage devices. Here we present a facile and scalable fabrication of metal oxide nanobranches on ALD pre-formed TiO2 nanotubes. The metal oxide branches can be a wide range (nearly any) of desirable materials, including NiO and Co3O4 demonstrated herein. As an example, the TiO2/NiO nanoarray battery cathode exhibits a relatively high gravimetric capacity value of [similar]153 mA h g−1 and a fairly good stability up to 12 000 cycles with a capacitance of 132 mA h g−1 at 2 A g−1.